2018
DOI: 10.4172/2324-8602.1000343
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression and Hypertension Comorbidity in HIV/AIDS Patients at Kenyatta National Hospital HIV Care Centre, Nairobi, Kenya

Abstract: Chronic inflammation in HIV disease is sustained by immune reconstitution that results from use of combination therapy by patients and manifested by increased expression of inflammatory cytokines. Chronic inflammation in HIV disease is associated with endothelial dysfunction of the cardio vasculature giving rise to reduced elasticity resulting in high blood pressure. This state is marked by increased IL-6 cytokine expression as manifested in patients with type 2 diabetes and hypertension. This study sought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Pathophysiologic mechanisms of hypertension in PLWH are a combination of typical, well-known factors occurring in the general population and the chronic inflammation resulting from HIV infection. It has been reported that higher levels of IL-17 A, IFN-γ, IL-6, and CRP were significantly associated with hypertension in ART-treated PLWH [ 75 ]. Moreover, the levels of intermediate monocytes CD14 + 16 + were increased with higher HIV viral load, and this may lead to microbial translocation that drives systemic inflammation [ 76 ].…”
Section: Modifiable Cvd Risk Factors In Plwhmentioning
confidence: 99%
“…Pathophysiologic mechanisms of hypertension in PLWH are a combination of typical, well-known factors occurring in the general population and the chronic inflammation resulting from HIV infection. It has been reported that higher levels of IL-17 A, IFN-γ, IL-6, and CRP were significantly associated with hypertension in ART-treated PLWH [ 75 ]. Moreover, the levels of intermediate monocytes CD14 + 16 + were increased with higher HIV viral load, and this may lead to microbial translocation that drives systemic inflammation [ 76 ].…”
Section: Modifiable Cvd Risk Factors In Plwhmentioning
confidence: 99%